2020
DOI: 10.3102/0162373720906217
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Coaching in a Simulated Environment

Abstract: This article evaluates whether providing coaching between practice sessions in teacher education courses leads to more rapid development of skills and changes in teachers’ beliefs about student behavior, using mixed-reality simulations as a practice space and standardized assessment platform. We randomly assigned 105 prospective teachers to different coaching conditions between simulation sessions integrated into a teacher preparation program. Coached candidates had significant and large improvements on skills… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
113
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(136 citation statements)
references
References 87 publications
4
113
0
19
Order By: Relevance
“…We hypothesize that it is not the simulation experience in and of itself that promotes teachers' learning, but it is the simulation experience coupled with opportunities to reflect on one's practice and to debrief this experience with peers and knowledgeable others that support teachers in learning how to engage in ambitious practices like facilitating argumentation‐focused discussions. In fact, recent research (Cohen, Wong, Krishnamachari, & Berlin, 2020) has suggested that teacher learning is best supported by specific and targeted feedback from knowledgeable others—in this case, a coach—on key aspects of practice, and that coaching results in more rapid learning for novice teachers than self‐reflection alone.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that it is not the simulation experience in and of itself that promotes teachers' learning, but it is the simulation experience coupled with opportunities to reflect on one's practice and to debrief this experience with peers and knowledgeable others that support teachers in learning how to engage in ambitious practices like facilitating argumentation‐focused discussions. In fact, recent research (Cohen, Wong, Krishnamachari, & Berlin, 2020) has suggested that teacher learning is best supported by specific and targeted feedback from knowledgeable others—in this case, a coach—on key aspects of practice, and that coaching results in more rapid learning for novice teachers than self‐reflection alone.…”
Section: Discussionmentioning
confidence: 99%
“…Dyment and Downing (2020), however, state that if research, practice and policy fail to connect online initial teacher education (ITE), the student experience and graduate learning outcomes may be hampered. Interestingly, Cohen et al (2020) have recently reported a successful approach with regards a combined synchronous and asynchronous coaching of pre-service teachers in simulated online learning environments. Specifically, the authors found an increased effect of the combined synchronous and asynchronous approach, when compared to asynchronous coaching only in simulated learning environments.…”
Section: Expectations On Teacher Education Programmes Moving Towards mentioning
confidence: 99%
“…Particularly related to the COVID-19 situation, PE is being internationally advocated as a critical face-to-face experience for students (EUPEA 2020), which can be explored by the programmes to improve and update the quality of the provision to their pre-service teachers. Interestingly, all programmes referred to the programmespecific strengths, in how the professional qualification of the programme was an important strength, underlined by the school placement experience (all partners) and the programme curriculum (all partners), which consists of a balanced range of learning opportunities, including experiential and ICT components, despite the need for a better articulation of the online environment (Dyment and Downing 2020;Cohen et al 2020). Following Allen and Seaman (2013) classification, the five programmes could be classified as web-facilitated (1-29% online), with clear potential to transition to a blended/hybrid model (30-79% online).…”
Section: Strengthsmentioning
confidence: 99%
See 2 more Smart Citations